2022
DOI: 10.3390/universe8100501
|View full text |Cite
|
Sign up to set email alerts
|

Quiescent Optical Solitons with Kudryashov’s Generalized Quintuple-Power and Nonlocal Nonlinearity Having Nonlinear Chromatic Dispersion

Abstract: The paper derives stationary optical solitons with nonlinear chromatic dispersion. A nonlocal form of nonlinearity and quintuple power–law of nonlinearity are considered. The Kudryashov’s integration scheme enables to retrieve such solitons. A plethora of solitons come with this algorithm.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…These include the Painleve analysis, retrieval of solitons, and conservation laws with the usage of the undetermined coefficients and the multiplier approach respectively. Later, the trial equation approach was also implemented to recover the soliton solutions to the model [3][4][5][6][7]. Further down the road, several more studies were conducted.…”
Section: Introductionmentioning
confidence: 99%
“…These include the Painleve analysis, retrieval of solitons, and conservation laws with the usage of the undetermined coefficients and the multiplier approach respectively. Later, the trial equation approach was also implemented to recover the soliton solutions to the model [3][4][5][6][7]. Further down the road, several more studies were conducted.…”
Section: Introductionmentioning
confidence: 99%
“…The evolution of quiescent optical solitons has gained momentum and extreme importance ever since its first appearance about two decades ago [1][2][3][4][5]. The study of such solitons with nonlinear chromatic dispersion (CD) revealed quite a few results that have been reported all across the board [6][7][8][9][10]. Several models with nonlinear CD and various forms of self-phase modulation (SPM) structures have been studied [11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…As a result, until recently, the focus has been on managing CD rather than eliminating it altogether. Although studies on CD management and measurement date back to the 1980s, CD was formally introduced into the literature by Yan et al in 2006 [20], and CD-related investigations have remained among the most prominent topics in the realm of nonlinear optics [21][22][23][24][25][26][27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%